Electric Vehicle Strategies: A Literature Review on Their Impact on Firm Performance and Market Value - Kumalawati, Nanda Ismi; Noveria, Ana (Journal Research of Social Science, Economics, and Management, 2026)
Prior literature plays a central role in strengthening theoretical foundations and explaining relationships among variables within a scientific study. This article conducts a structured literature review to examine how electric vehicle (EV) adoption strategies influence firm performance and market value. Although prior research investigate different aspects of green innovation, product variety, R&D, sustainability, and advertising, this review integrates those findings into a unified EV strategy perspective. The aim of this article is to build theoretical propositions for future empirical research. The results of this literature review show that: (1) EV adoption strategies, represented through green vehicle innovation, EV product portfolio expansion, sustainable operations, R&D intensity, and green marketing, exhibit mixed effects on firm performance. While EV sales growth, eco-innovation, and R&D investment often enhance efficiency and competitiveness, excessive product variety and certain sustainability efforts may reduce performance due to increased complexity and short-term costs; (2) The effect of EV adoption strategies on market value is also heterogeneous. Incremental innovation, R&D investment, and credible patent activity generally support firm valuation, whereas green innovation and sustainability investments may trigger short-term valuation declines when uncertainty and capital intensity are high.